Epistemology of Al-Razi's Philosophical Thought - Maspuroh; Emi Nuraemi; Risma Euis Patonah; Rismayanti (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2025)
Islamic civilization has given birth to many great and famous philosophers and scientists in their respective fields. Al-Razi was one of the scientists in the Islamic world, and had a great influence on European science and medicine. Abu Bakar Muhammad bin Zakariya al-Razi (865-925 AD), he is known as one of the leading scientists, philosophers and doctors in Islamic civilization. His thinking is rational and humanist. brought great influence in various fields, especially in the fields of philosophy and medicine. One of al-Razi's most controversial philosophical contributions is his concept of al-Qudama al-Khomsa or the five eternals. In this view, al-Razi proposed five eternal entities: God, soul, matter, time, and space. In contrast to the dominant theological views of its time, this concept emphasized a rational approach aimed at explaining the origin of the universe metaphysically. In the figure of Al-Razi, the qualifications of the theocentric paradigm as well as the anthropocentric paradigm were gathered but rejected the “concept of prophecy” which put him in big trouble and received the verdict of al-mulhid (atheist).